CONTOUR 2009 : Fourth Biennial of Moving Image : Hidden in Remembrance is the Silent Memory of our Future. - Gregos, Katerina; Roelandt, Els (Ghent : vzw Mark (A Prior Magazine), The Royal Academy of Fine Arts (KASK) of the University College Ghent, 2009)
Ahtila, Eija-Liisa ; Asselberghs, Herman ; Bartana, Yael ; Berg, Lene ; Borremans, Michaël ; Buckingham, Matthew ; Bunte, Andreas ; Delat, Chto ; Jafri, Maryam ; Maljkovic, David ; Meessen, Vincent ; Mellors, Nathaniel ; Rosefeldt, Julian ; Sanders, Mira ; Sapountzis, Yorgos ; van Oldenborgh, Wendelien ; von Brandenburg, Ulla ; Wilcox, T.J.
Contour 2009, the 4th Biennial of Moving Image, Mechelen, 15 August - 18 October 2009
boek